Maternofetal Thyroid Action and Brain Development - Ahmed, R.G. (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
Thyroid hormones (THs) are a key regulatory factor of the developmental program and maternal-fetal communication network. The cellular basis for these effects lies in the organizational role of TH in neuronal migration, synaptogenesis and differentiation of multiple cell types. Thus, any vigorous changes in the THs levels during the development may cause a patho-physiological states and serious damage to the structural development and organization of the brain. It can be hypothesized that the disturbance in the maternofetal THs due to antithyroid drugs, Levo-thyroxine or environmental disruptors may lead, in turn, to the biochemical dysfunctions, morphofunctional alterations, developmental abnormalities and brain damage if not corrected prior/after the birth. Thus, further studies need to be done to emphasize this concept.